Marine algal polysaccharides alleviate aflatoxin B1-induced bursa of Fabricius injury by regulating redox and apoptotic signaling pathway in broilers - Guo, Yan (Poult Sci, 2020)
Aflatoxin B1 (AFB1) causes toxic effect and leads to organ damage in broilers. Marine algal polysaccharides (MAP) of Enteromorpha prolifera exert multiple biological activities, maybe have a potential detoxification effect on AFB1, but the related research in broilers is extremely rare. Therefore, the purpose of this study was to investigate whether MAPs can alleviate AFB1-induced oxidative damage and apoptosis of bursa of Fabricius in broilers. A total of 216 five-week-old male indigenous yellow-feathered broilers (with average initial body weight 397.35 ± 6.32 g) were randomly allocated to one of three treatments (6 replicates with 12 broilers per replicate), and the trial lasted 4 wk. Experimental groups were followed as basal diet (control group); basal diet mixed with 100 μg/kg AFB1 (AFB1 group, the AFB1 is purified form); basal diet with 100 μg/kg AFB1 + 2,500 mg/kg MAPs (AFB1 + MAPs group). The results showed that the diet with AFB1 significantly decreased the relative weight of bursa of Fabricius (P < 0.05), antioxidant enzymes activities of total superoxide dismutase (T-SOD), catalase (CAT), glutathione peroxidase (GSH-Px), glutathione S-transferase (GST), and total antioxidation capacity (T-AOC), while increased malondialdehyde (MDA) content (P < 0.05). Besides, compared with AFB1 group, dietary MAPs improved the relative weight of bursa of Fabricius and activities of antioxidant enzymes (T-SOD, GSH-Px, CAT, GST) with decreased MDA contents (P < 0.05). Moreover, the consumption of AFB1 downregulated the mRNA expression of SOD1, SOD2, GSTA3, CAT1, GPX1, GPx3, GSTT1, Nrf2, HO-1, and p38MAPK (P < 0.05). Dietary MAPs upregulated the mRNA expression of SOD2, GSTA3, CAT1, GPX1, GSTT1, p38MAPK, Nrf2, and HO-1 in comparison with AFB1 group (P < 0.05). The histological analysis confirmed restoration of apoptotic cells of bursa of Fabricius (P < 0.01), which seen with MAPs supplemented broilers. Besides, dietary MAPs down-regulated the mRNA expression of caspase-3 and Bax (P < 0.05), while up-regulated the mRNA expression of Bcl-2 (P < 0.05) compared with AFB1 group. In addition, according to protein expression results, dietary MAPs up-regulated the protein expression level of antioxidant and apoptosis-associated proteins (Nrf2, HO-1, p38MAPK, Bcl-2) (P < 0.01), but down-regulated the protein expression level of caspase-3 and Bax (P < 0.01). In conclusion, dietary MAPs alleviated AFB1-induced bursa of Fabricius injury through regulating Nrf2-mediated redox and mitochondrial apoptotic signaling pathway in broilers.